2015
DOI: 10.1366/14-07495
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Cerium Oxide Nanoparticles on Rice, Wheat, and Barley Roots: A Fourier Transform Infrared (FT-IR) Microspectroscopy Study

Abstract: Cerium oxide nanoparticles (nCeO2) have extensive industrial applications, and concerns regarding their threat to the environment have been raised. This study includes structural analysis of intact root xylem of rice (Oryza sativaL.), wheat (Triticum aestivumL.), and barley (Hordeum vulgareL.) seedlings exposed to nCeO2 suspensions (0, 62.5, 125, 250, and 500 mg L(-1)). Fourier transform infrared microspectroscopy was applied to determine compositional alterations in the root xylem, and principal component ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 40 publications
(87 reference statements)
3
24
1
Order By: Relevance
“…For this reason, we focused on both Ce and macronutrient accumulation in barley kernels. In agreement with the findings from López-Moreno et al (2010), Zhao et al (2015), and Rico et al (2015), we did not observe any significant difference among the treatments for kernel Ce concentrations. Our results suggest that translocation of nCeO2 into barley kernels is rather unlikely.…”
Section: Barley Life Cycle and Cerium Accumulationsupporting
confidence: 91%
See 1 more Smart Citation
“…For this reason, we focused on both Ce and macronutrient accumulation in barley kernels. In agreement with the findings from López-Moreno et al (2010), Zhao et al (2015), and Rico et al (2015), we did not observe any significant difference among the treatments for kernel Ce concentrations. Our results suggest that translocation of nCeO2 into barley kernels is rather unlikely.…”
Section: Barley Life Cycle and Cerium Accumulationsupporting
confidence: 91%
“…Zhao et al (2013) did not observe negative effects on biometric parameters in plants of Cucumis sativum with nCeO2. On the opposite, Rico et al (2015) reported that nCeO2 500 mg kg -1 increased the height of barley plants and promoted the accumulation of DM in plant shoots.…”
Section: Barley Life Cycle and Cerium Accumulationmentioning
confidence: 95%
“…Alterations were also observed in the DNA/RNA region (∼950 cm −1 ) at both sites, which may suggest exposure to genotoxic agents. 14,35 In addition, peaks associated with terpenes 36 were discovered at both sites (1447 cm −1 in Site 2 leaves, 1369 and 1454 cm −1 in Site 3 leaves). Several terpenes, particularly carotenoids are known to function as scavengers of ROS, 37 implying that leaves from polluted sites may have been exposed to higher ROS levels, possibly as a result of increased pollution exposure.…”
Section: Resultsmentioning
confidence: 93%
“…Further analysis indicated that nCeO 2 caused genotoxic effects in soybean . Germination also was unaffected by nCeO 2 in rice ( Oryza sativa ), wheat ( Triticum aestivum ), and barley ( Hordeum vulgare ) . Tumburu et al found accelerated germination and early seedling development in Arabidopsis thaliana with nCeO 2 treatment.…”
Section: Resultsmentioning
confidence: 99%